A political-economy model to reduce fire and improve livelihoods in Indonesia's lowlands - Purnomo, H.; Kusumadewi, S.D.; Ilham, Q.P.; Puspitaloka, D.; Hayati, D.; Sanjaya, M.; Okarda, B.; Dewi, S.; Dermawan, A.; Brady, M.A. (Elsevier, 2021)
Deforestation and land degradation have been occurring across the globe, particularly in developing countries. Over the past 30 years, Indonesia's lowlands have experienced rapid degradation, deforestation and fires. Interventions aimed to achieve sustainable lowlands have been made through the introduction and adoption of commodities that provide sufficient livelihoods and reduce fires. However, these interventions have not guaranteed success as the contribution of the governance and political economy towards sustainability is poorly understood. This study aims to determine how governance and political-economic factors affect sustainability of lowland agriculture. We used structural equation modeling (SEM) to understand the effect of political economy factors (structure, institution and actor) on sustainability and community livelihoods in Indonesian lowlands. Data were collected through interviews with selected respondents. We found Structure, Institution, and Actor explain 31% (0.31) of the variation in the Sustainability and Livelihoods model. The remaining effects were explained by non-political economic factors. Using actor-centered power (ACP) and social network analysis (SNA) approaches, we also identified and assessed different actors' power and their networks. The central government and private companies are the most powerful actors, while farmers are the least powerful actors. The findings demonstrate that considering governance and political-economic factors in designing and implementing commodity interventions for policy makers is a must. Devolving power to farmers is crucial in achieving power balance among various actors, which leads to better political economy condition that affects sustainability of lowlands.